2008
DOI: 10.1258/acb.2008.007259
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of variability in HbA1c as assessed by simultaneously measuring fructosamine and use of error grid analysis

Abstract: HbA1c may not accurately reflect glucose control. Our method, utilizing co-assessment with serum fructosamine, evaluates the possible clinical impact of this. We suggest the analysis used in this paper should be used routinely in diabetes practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…These deviations in mean blood glucose and the A1C value are called the glycohemoglobin index (GHI), and the biological variation of A1C has been examined [3,4,42,43]. The G-gap is also reported to be an indicator with biological variation [5,31], and Nayak et al [6] reported that the G-gap has consistent biological variability in individuals. Recently, as mentioned above, fructosamine or GA and G-gap have been reported as predictive indicators for diabetic complications independent of A1C [16,17,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These deviations in mean blood glucose and the A1C value are called the glycohemoglobin index (GHI), and the biological variation of A1C has been examined [3,4,42,43]. The G-gap is also reported to be an indicator with biological variation [5,31], and Nayak et al [6] reported that the G-gap has consistent biological variability in individuals. Recently, as mentioned above, fructosamine or GA and G-gap have been reported as predictive indicators for diabetic complications independent of A1C [16,17,32].…”
Section: Discussionmentioning
confidence: 99%
“…For the G-gap, following the reports of Macdonald et al [31] and Nayak et al [6], fructosamine was replaced with GA, and GA-derived A1C = {[(GA−GA(M))/ GA(SD)] × A1C (SD)} + A1C (M) was obtained. The G-gap was then obtained as G-gap = the HbA1c measured value − the GA-derived A1C (M and SD indicate mean and standard deviation, respectively).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This categorization was taken from our previously published clinical error grid analysis of the impact of G-gap on assessment of glycemic control (19). …”
Section: Methodsmentioning
confidence: 99%
“…37 Some studies have reviewed the usefulness of FA. [37][38][39] It has been suggested that FA testing should be performed as a routine check in diabetes patients with normal HbA1c concentrations to confirm that their glucose is under control. 37 This study measured MAGE c and MAGE gos with CGMS data as markers for glucose variability.…”
mentioning
confidence: 99%